Geographic and Socioeconomic Determinants of Healthcare Utilization at Faisal Islamic Hospital, Makassar - Saru, Amaliah Amriani Amran; Taiyeb, A. Mushawwir; Akbar, Muh. Syaiful; Wafaretta, Erona (Journal of Scientific Insights, 2025)
Utilization of hospital services varies according to patient characteristics. As Faisal Islamic Hospital Makassar serves both urban and non-urban populations, understanding the determinants of service utilization is essential for improving equitable access. This study examined the influence of geographic and socioeconomic factors on outpatient service utilization. A cross-sectional study was conducted involving 99 outpatients. Service utilization was categorized as new versus return visits, while independent variables included education, occupation, income, and residential location. Chi-square tests with a 95% confidence level were used for analysis. Income (p = 0.026) and residential location (p = 0.019) were significantly associated with service utilization, whereas education (p = 0.363) and occupation (p = 0.165) were not. Patients with higher income and those living within the city were more likely to make return visits. These findings highlight the need for service strategies that maintain quality for frequent users while enhancing access for lower-income and out-of-city patients.